Lithium Doping Enhances the Aqueous Zinc Ion Storage Performance of V3O7 ⋅ H2O Nanorods - Yingfang Hu; Siwen Zhang; Yujin Ren; Rongyuan Ge; Yaowen Shi; Xinyu Feng; Hui Li; Baohua Jia; Bosi Yin; Tianyi Ma (ChemElectroChem)
Abstract Aqueous zinc‐ion batteries (AZIBs) offer significant advantages, including high safety, environmental protection and abundant zinc sources. V‐based layer‐like oxides are promising candidates as cathode materials for ZIBs; however, they face challenges such as low electrical conductivity, poor cycling stability, and limited Zn2+ storage capacity. In this study, Li‐V3O7 ⋅ H2O electrode materials were successfully synthesized using a hydrothermal method. The doping of lithium ions has led to a significant expansion of the interlayer spacing within the electrode structure, which enhances ion mobility and improves ion transport speed as well as charge‐discharge rates. Additionally, the increased spacing allows for the accommodation of more zinc ions, resulting in greater specific capacity and energy storage. More importantly, this modification reduces structural strain, minimizes the dissolution of vanadium‐based materials, and maintains electrode integrity over multiple cycles, thereby improving cycling stability. Consequently, the properties of V3O7 ⋅ H2O electrodes were substantially enhanced through lithium‐ion doping. The Li‐V3O7 ⋅ H2O cathode has a specific capacity of 411.8 mAh g−1 at low current and maintains 83 % of its capacity at 4.0 A g−1 for 4800 cycles, indicating a noteworthy improvement over pristine V3O7 ⋅ H2O. Exhibiting outstanding conductivity, discharge capacity, and cycling stability, it holds immense promise for future high‐performance energy storage.